Implementasi Collaborative Governance Dalam Pelayanan Keimigrasian: Studi Pada Kerja Sama Antara Kantor Imigrasi dan Mal Pelayanan Publik - Akhmad Aditya Jonea Firmansyah; Seno Setyo Pujonggo; Habbi Firlana (Badan Penerbit STIEPARI Press, 2025)
This study aims to analyze the implementation of collaborative governance in immigration services through a case study of the cooperation between the Immigration Office and the Public Service Mall (MPP). A qualitative approach with a case study method was used to explore the dynamics, challenges, and successes of inter-agency collaboration in the context of public service delivery. The findings indicate that this collaboration improves service effectiveness, shortens processing time, and increases public satisfaction. However, several challenges remain, including inter-institutional coordination, limited technological infrastructure, and differences in organizational culture that must be addressed strategically. This research contributes to the development of collaborative governance in the public sector and highlights the importance of system integration and community participation in building sustainable services.